Cloning, Expression of Δ5-Elongase gene from Pavlova sp. CCMP459 and Determination of polyunsaturated fatty Acid production in Physcomitrella patens - Pichit Chodok (Prince of Songkla University, 2014)
Doctor of Philosophy (Pharmaceutical Sciences), 2012